THE EFFECTIVENESS OF THE LINGUOCULTURAL APPROACH IN FOREIGN LANGUAGE TEACHING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The aim of this paper is to provide information on extracurricular activities and their potential benefits on students’ educational development and to understand their importance in a wide range of educational settings by analyzing related works of literature. This study examines the impacts of ECA membership on various educational outcomes as well as the reliability of the measurements employed in earlier research, paying special attention to evidence of causal effects.